2016
DOI: 10.1016/j.scitotenv.2016.06.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fertilising with pig slurry and chicken manure on GHG emissions from Mediterranean paddies

Abstract: Soil fertilisation affects greenhouse gas emissions. The objective of this study was to compare the effect of different fertilisation strategies on N2O, CH4 emissions and on ecosystem respiration (CO2 emissions), during different periods of rice cultivation (rice crop, postharvest period, and seedling) under Mediterranean climate. Emissions were quantified weekly by the photoacoustic technique at two sites. At Site 1 (2011 and 2012), background treatments were 2 doses of chicken manure (CM): 90 and 170kgNH4(+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 84 publications
0
14
0
3
Order By: Relevance
“…A adição de fertilizantes orgânicos é considerada fonte de energia para os microrganismos do solo (SÁ et al, 2014 O aproveitamento de compostos orgânicos de fácil decomposição como substrato para o crescimento microbiano no solo é responsável por boa parte das emissões de CO 2 na fase inicial após a aplicação, considerando que estas emissões provêm do material orgânico aplicado, sendo maior nos primeiros 15 dias, com posterior redução, segundo Maris et al (2016).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…A adição de fertilizantes orgânicos é considerada fonte de energia para os microrganismos do solo (SÁ et al, 2014 O aproveitamento de compostos orgânicos de fácil decomposição como substrato para o crescimento microbiano no solo é responsável por boa parte das emissões de CO 2 na fase inicial após a aplicação, considerando que estas emissões provêm do material orgânico aplicado, sendo maior nos primeiros 15 dias, com posterior redução, segundo Maris et al (2016).…”
Section: Resultsunclassified
“…Houve um pico de emissão diária no 4º dia de coleta, o que pode ser resultado do estímulo provocado pela adição de água ao solo. Maris et al (2016) também observaram estímulo à população microbiana pela variação nos teores de água no solo. A adição de palha representa aporte de energia e nutrientes, o que estimula a população microbiana e aumenta sua atividade metabólica, ocasionando maior emissão de CO 2 .…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Studies focusing on the influence of organic fertilizers on GHG emissions under flooded rice systems have been carried out in different regions for evaluating products such as straw [6,17,18], green manure [19,20], pig manure [21], pig slurry and chicken manure [22], and anaerobically digested pig slurry (ADPS) [23]. The most consistent result found in the literature is that the incorporation of crop residues increases methane emissions due to the additional C input [6,17,24].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [29] found significant increases in CH 4 emissions by applying ADPS. Under Mediterranean rice conditions, only Maris et al [22] studied the application of PS to flooded rice, and their results showed no significant differences in GHG emissions and GWP for PS fertilization compared to ammonium fertilization. Thus, more studies focusing on the substitution of mineral fertilizers with organic fertilizers to evaluate the effect on GHG emissions are needed in the framework of a more sustainable agriculture.…”
Section: Introductionmentioning
confidence: 99%